Disrupting Neoliberalism’s Ideologies: From Civil Death to Civil Disobedience in Madrid’s Right to Housing Movement - Gonick, Sophie (Urban, 2016)
In this paper, I am concerned primarily with the formation of alternative practices that challenge hegemonic ideologies. In particular, I look to the ways in which Madrid’s right to housing movement resists and disrupts the dominant ideology of neoliberalism, particularly neoliberal housing policy. For generations of scholars, ideology has held a variety of meanings: it can imply distortion or fanaticism, structuring systems of oppression, silencing some while giving voice to others. Herein I am concerned with how neoliberal ideology reconfigures citizenship into a regime of consumption and participation in the marketplace, and how housing becomes a key arena in which we can observe such a transformation. In this paper, I ask: what happens when people face complete exclusion from such a regime?